Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Solve for y
2x-3y+6=0


Sagot :

 2x - 3y + 6 = 0
              - 6  - 6
       2x - 3y = -6
2x - 2x - 3y = -6 - 2x
             -3y = -6 - 2x
              -3        -3
                y = 2 + ²/₃x